Duodenal Diverticuli. Statistical Analysis of 59 Cases - Besenzoni, Raúl; Armand Ugon, Alfredo; Harretche, Martín (Cirugía del Uruguay, 1979)
Analysis of 59 case hystories of duodenal diverticun diagnosed by radiology, surgery or fibroscopy is done. 50 o/o ,of patients were o er 50 years of age;_ there were no sex predominance; topography was 80 o/o in D. II; and in general they were of the single type.